Coaching and mentoring (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. Everyone has their own image of a good leader. Some believe that leadership is about commanding respect from your employees so they won't hesitate to follow orders. Others think it's about building trust and making people want to work with and for you and your vision. A leader should be a coach and a mentor to those who follow them. Leadership is not about holding a firm grip of authority over others. It's about helping them develop and grow so that they can be active contributors to your aligned goals. In this podcast, we identify what it takes to be a) a great coach and b) a great mentor. Learning Objectives Distinguish the differences between coaching and mentoring Identify areas in which a coach is beneficial, and how one goes about coaching Identify areas in which a mentor is beneficial, and how one goes about mentoring.